Skewness Expectations and Portfolio Choice - Tilman Drerup; Matthias Wibral; Christian Zimpelmann (Institute of Labor Economics (IZA), 2022)
Many models of investor behavior predict that investors prefer assets that they believe to have positively skewed return distributions. We provide a direct test of this prediction in a representative sample of the Dutch population. Using individual-level data on return expectations for a broad index and a single stock, we show that portfolio allocations increase with the skewness of respondents' return expectations for the respective asset, controlling for other moments of a respondents' expectations and sociodemographic information. We also show that while an individuals' expectations are correlated across assets, sociodemographics only capture very little of the substantial heterogeneity in expectations.
Keywords: D14; D84; G02; G11; 330; behavioral finance; portfolio choice; skewness; stock market expectations